Processo de produção de composto orgânico derivado de resíduos industriais com aplicação no cultivo de alface - Tarrento, Gilson Eduardo [UNESP] (2008)
It is assumed that there is generation condition in every production process. Alternative ways for the correct destination of the residues has become essential. Therefore, an experiment on different industrial solid residues compound from medicinal plants active principle extration has been performed. The experiment was based on the mixture of the residues in different proportions: a) organic residue generated from jambu (Spilanthes oleracea) smashing after active principle extraction, b) physiochemic mud generated from water treatment process and c) biologic mud originated from the company sewage. This work aimed at generating an environmentally correct alternative for phisiochemic mud reutilization and verify the agronomic effects of the resulting compounds in lettuce production. The compounding process lasted 120 days. Piles temperature was measured in three different depths. At the end, the compound was weighed and the average yield was evaluated. In the second phase of the experiment we aimed at evaluating the compound agronomic effects on lettuce (Lactuca sativa L.) production. The compounded materials were placed ins vases in greenhouses in an entirely randomized order, with factorial 4 x 4. Factor 1 was formed by 4 treatments: compound 1 (C1 - 0% mud - 100% jambu), compound 2 (C2 - 7% mud - 93% jambu), compound 3 (C3 - 13% mud - 87% jambu), compound 4 (C4 - 26% mud - 74% jambu). Factor 2 was formed by 4 differente compound dosages: (0,45, 90 e 135 t ha-¹) and hour repetitions, totaling 64 experomental unities. Treatment C1, dosage 3 (90 t ha-¹) presented the best results in the evaluation 45 days after lettuce transplantation. In the remaining treatments there was alinear decrease in lettuce production. However, C4 that 26% mud in its composition was superior than those with 0 dosage of organic matter. Compound can be considered an environmentally correct alternative for these residues with the possibility of agronomic utilization.